2013
DOI: 10.1186/2049-2618-1-28
|View full text |Cite
|
Sign up to set email alerts
|

Colonization patterns of soil microbial communities in the Atacama Desert

Abstract: BackgroundThe Atacama Desert is one of the driest deserts in the world and its soil, with extremely low moisture, organic carbon content, and oxidizing conditions, is considered to be at the dry limit for life.ResultsAnalyses of high throughput DNA sequence data revealed that bacterial communities from six geographic locations in the hyper-arid core and along a North-South moisture gradient were structurally and phylogenetically distinct (ANOVA test for observed operating taxonomic units at 97% similarity (OTU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
155
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(181 citation statements)
references
References 64 publications
18
155
5
Order By: Relevance
“…Gammaproteobacteria was found in moderately high abundance in whales (33.9%) and 50% in salamanders, and was shared in varying amounts amongst all the wild vertebrates sampled. One class, Thermoleophilia, is only found on bats and dogs, suggesting a relationship to terrestrial mammals, however it is a known soil organism (Suzuki and Whitman, 2012; Crits-Christoph et al, 2013). For all of the vertebrates examined for this study, 7.6%–49.4% of bacteria were not in the most abundant taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Gammaproteobacteria was found in moderately high abundance in whales (33.9%) and 50% in salamanders, and was shared in varying amounts amongst all the wild vertebrates sampled. One class, Thermoleophilia, is only found on bats and dogs, suggesting a relationship to terrestrial mammals, however it is a known soil organism (Suzuki and Whitman, 2012; Crits-Christoph et al, 2013). For all of the vertebrates examined for this study, 7.6%–49.4% of bacteria were not in the most abundant taxa.…”
Section: Discussionmentioning
confidence: 99%
“…4 Some regions in the desert were once thought to have 'Mars-like' soils deemed too extreme for life to exist given high levels of UV radiation, the presence of inorganic oxidants, areas of high salinity and very low concentrations of organic carbon. 5 However, recent research has revealed extraordinary bacterial diversity across a range of Atacama environments, 6,7 and many novel actinomycetes have been isolated from hyper-and extreme hyper-arid soils. 8,9 Biological and genome-guided screening of some of these actinomycetes has led to the isolation and characterization of new natural products belonging to diverse structural classes and exhibiting various biological activities, as exemplified by the antimicrobial chaxamycins and chaxalactins isolated from Streptomyces leeuwenhoekii C34 T , the abenquines from Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial diversity of rhizosphere soils from Atacama Desert differed from those of the other studied rhizosphere soils. The low bacterial diversity of rhizosphere soil from Atacama Desert may depend on vegetative state of bacterial cells (Crits-Christoph et al 2013) and/or water availability, salt, and nutrient content of these soils Vítek et al 2010).…”
Section: Discussionmentioning
confidence: 99%